Zakat and wakaf funded housing for the poor and needy – an analysis of the zakat and wakaf authorities roles from the authorities’ perspectives - Abdul Rashid, Khairuddin; Hasan, Sharina Farihah; Mohd Fauzi, Puteri Nur Farah Naadia; Aripin, Srazali; Ahmad Sarkawi, Azila (Malaysian Institute of Planners, 2018)
This paper concerns the provision of affordable housing for the poor and needy Muslims through zakat and wakaf funding. The study’s objectives are to determine whether zakat and wakaf resources are employed therein, examine the roles of the zakat and wakaf authorities, and identify constraints and the ensuing strategies. The study was carried out through desk research and interviews with representatives of selected zakat and wakaf authorities. Key findings from the study are that zakat and wakaf are involved in the provision of affordable housing for the poor and needy Muslims and that their funds have been employed therein. However, their roles are dissimilar, therefore, each authority has its own modus operandi. In addition, both zakat and wakaf authorities have constraints in the availability of expertise to undertake the procurement of housing development and they address this problem through collaborative working styles, with each other, and with private property developers.